Ethnobotanical survey of plants used in magico-religious practices in Kullu district of Himachal Pradesh, India. - Thakur, Smriti; Jamwal, Radhika; Negi, Subodh (Ethnobotany Research and Applications, 2023)
Background: Local inhabitants of Kullu region of Himachal Pradesh, use various sacred plants for pleasing and worshipping local ‘devats’, in various religious ceremonies, but we are losing the sacred valuable knowledge at a rapid pace, hence the need to document and preserve this knowledge. Method: Ethno-botanical survey, field visits were conducted in different parts of Kullu district. Indigenous people, shamans, tantric, and local elderly members of society were consulted to collect the data. Informal discussions and interviews were done for data collection. Different use categories, the basic variables like frequency of citation (FC), use reports (UR), the number of uses (NU) and the ethno-botanical indices like relative frequency of citations (RFC), relative importance index (RI), cultural importance index (CI), and cultural value index (CV) were determined and compared. Result: The paper includes the list of 75 species under 46 families, used for Magico-religious beliefs along with their medicinal value. Most utilized parts were flowers, whole plant, leaves, seeds, followed by fruits. Ficus religiosa L. showed highest value in all the indices (CI =2, RFC=1, RI= 0.75), with highest number of citation (FC=25), Use report (UR=50), followed by Ocimum sanctum L. Conclusion: To maintain the age-old faiths, people of these areas, harvest plants sustainably and economically, these practices contribute in the ex-situ conservation of plants while fulfilling their values in magico-religious beliefs, as well as sustainable development of the area. Study also reveals the status of 21 rare plant species which need conservation. Keywords: Sacred Plants, Religious Ceremonies, Ex-situ Conservation, Magico-religious beliefs, Sustainable Development